Inequality, Growth and Public Spending in Central, East and Southeast Europe - Mario Holzner (The Vienna Institute for International Economic Studies (wiiw), 2010)
The article analyses the joint determinants of inequality and growth with a special emphasis on public spending structures in transition. The mutual benefit of low real interest rates, to both equity and economic development is a major result of this paper. In terms of public spending items we find a positive correlation with equity and a negative with growth as several of the government expenditure items seem to act counter-cyclically. In the late 1990's and early 2000's the European integration process allowed most of the transition economies to aim for the best of both worlds equity and economic development.
Keywords: D63; H5; O4; P2; 330; inequality; government expenditures; economic growth; transition